The handmade marketplace - Chapin, Kari; Martin, Emily Winfield; Skelley, Jen (North Adams, MA Storey Pub, 2010)
Perhaps you want a second income stream. Maybe you're considering selling your work full time and leaving your 9-to-5 job behind. Exploring selling your work is an exciting endeavor
Getting to know yourself and your business. Setting the scene for success ; Branding your business ; Establishing basic business practices -- Spreading the word-- and images. Marketing basics ; Your craft community ; Blogging ; Advertising and publicity ; More online marketing networks -- Getting down to selling. The craft fair scene ; Selling in online stores ; Selling in brick-and-mortar stores -- Get creative: other selling options and opportunities
Includes index
1
Keywords: Handicraft industries; Selling -- Handicraft